OH defect contents in quartz in a granitic system at 1-5 kbar - Potrafke, Alexander; Ludwig, Thomas (Contributions to mineralogy and petrology, 2019)
Quartz is able to incorporate trace elements (e.g., H, Li, Al, B) depending on the formation conditions (P, T, and chemical system). Consequently, quartz can be used as a tracer for petrogenetic information of silicic plutonic bodies. In this experimental study, we provide the first data set on the OH defect incorporation in quartz from granites over a pressure/temperature range realistic for the emplacement of granitic melts in the upper crust. Piston cylinder and internally heated pressure vessel synthesis experiments were performed in a water-saturated granitic system at 1-5 kbar and 700-950 °C. Crystals from successful runs were analysed by secondary ion mass spectrometry (SIMS) and Fourier transform infrared (FTIR) spectroscopy, and their homogeneity was verified by FTIR imaging. IR absorption bands can be assigned to specific OH defects and analysed qualitatively and quantitatively and reveal that (1) the AlOH band triplet at 3310, 3378 and 3430 cm−1 is the dominating absorption feature in all spectra, (2) no simple trend of total OH defect incorporation with pressure can be observed, (3) the LiOH defect band at 3470-3480 cm−1 increases strongly in a narrow pressure interval from 4 kbar (220 µg/g H2O) to 4.5 kbar (500 µg/g H2O), and declines equally strong towards 5 kbar (180 µg/g H2O). Proton incorporation is charge balanced according to the equation H+ + A+ + P5+ = M3+ + B3+, with A+ = alkali ions and M3+ = trivalent metal ions.